(untitled) (Scientia Agropecuaria, 2025)
The agricultural sector faces risks from damage caused by phytopathogens, and many farmers rely on synthetic fungicides to combat them. However, excessive use of these products pollutes the environment and promotes pathogen resistance. This study evaluated the mycelial growth inhibition of 57 plant extracts against Botrytis cinerea, Lasiodiplodia theobromae, and Fusarium sp., and their efficacy in controlling Erysiphe necator in the field. It also evaluated their phytotoxic effect on wheat seeds and the identification of metabolites present in the extracts. The most effective extracts were those of Ambrosia artemisiifolia, Conyza sumatrensis, Dysphania ambrosioides, Minthostachis mollis, Salvia sp., Pimpinella anisum, and Syzygium aromaticum. The P. anisum extract exhibited the greatest inhibition of B. cinerea growth in tomatoes, while the most effective extracts against E. necator were P. anisum, C. sumatrensis, and S. aromaticum. Furthermore, the A. artemisiifolia extract exhibited phytotoxic effects on wheat seed growth. Flavonoids, tannins, steroids, triterpenoids, alkaloids, leucoanthocyanidins, coumarins, and saponins were identified as the main metabolites in the extracts. These results offer viable alternatives for controlling phytopathogenic fungi using plant extracts, contributing to a more sustainable agriculture that is less dependent on chemicals.